Endoscopy‐assisted transanal repair of afferent limb obstruction and long efferent limb with ileopexy after ileal J‐pouch‐anal anastomosis. Issue 2 (May 2016) - Araki, Toshimitsu; Okita, Yoshiki; Kawamura, Mikio; Kondo, Satoru; Kobayashi, Minako; Ohi, Masaki; Toiyama, Yuji; Tanaka, Koji; Inoue, Yasuhiro; Uchida, Keiichi; Mohri, Yasuhiko; Kusunoki, Masato
Abstract: Afferent limb obstruction can be a persistent complication after restorative proctocolectomy with ileal pouch‐anal anastomosis. We present a case of afferent limb obstruction complicated by a long efferent limb of the ileal pouch that we successfully treated with side‐to‐side anastomosis of the afferent and efferent limbs. The procedure involved using a transanal endoscopic stapling device assisted by transanal endoscopy with a thin intestinal video endoscope. This allowed reliable, safe visualization of the lesion from the tight pouch‐anal anastomosis and facilitated repair with an endoscopic stapling device. Because the technique was performed without enterotomy, it reduced the risks of contamination and leakage from transabdominal small bowel anastomosis. Laparotomy view also prevented of injury to the pouch itself and entrapment of the mesentery of the afferent and efferent limbs of the pouch between the stapler anvils.